2011
DOI: 10.1119/1.3535580
|View full text |Cite
|
Sign up to set email alerts
|

Studio optics: Adapting interactive engagement pedagogy to upper-division physics

Abstract: The use of interactive engagement strategies to improve learning in introductory physics is not new, but have not been used as often for upper-division physics courses. We describe the development and implementation of a Studio Optics course for upper-division physics majors at Kansas State University. The course adapts a three-stage Karplus learning cycle and other elements to foster an environment that promotes learning through an integration of lecture, laboratories, and problem solving. Some of the instruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…11), few have documented the process and made their experiences public (though there are notable exceptions 12,13 including a particularly noteworthy implementation of Studio in an upper-division course). 14 Given the significant investment involved in implementing Studio Physics, one of our major goals at CSM has been to study and document our secondary implementation process in sufficient detail to identify factors contributing to and impeding success, in order to maximize our own effectiveness and to inform other similar transitions.…”
Section: Introductionmentioning
confidence: 99%
“…11), few have documented the process and made their experiences public (though there are notable exceptions 12,13 including a particularly noteworthy implementation of Studio in an upper-division course). 14 Given the significant investment involved in implementing Studio Physics, one of our major goals at CSM has been to study and document our secondary implementation process in sufficient detail to identify factors contributing to and impeding success, in order to maximize our own effectiveness and to inform other similar transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on optics education spans a variety of topics, including the development of multimedia activities [11], online materials [12], and interactive learning strategies meant to be implemented in lecture courses [13] or hybrid lecture-studio courses [14]. In a course for preservice teachers, Atkins and Salter [15] described students' processes for constructing definitions of "blurriness."…”
Section: A Teaching and Learning In Optics Coursesmentioning
confidence: 99%
“…Other upper-division PER work has investigated the improvement of learning outcomes and student attitudes after a careful re-structuring of large parts of the curriculum or of the learning goals of courses [6][7][8]. Two examples of course transformations are the work to implement active learning in an intermediate optics laboratory at Indiana University-Purdue University Indianapolis [9], and the work at Kansas State University to implement the studio format for instruction in an upper-division optics lecture course [10]. Limitations of both studies are that the sample sizes were very small (7 and 15, respectively), and each study reported the results from a single year with no comparison made with their prereform counterparts.…”
Section: A Existing Per Literature On the Effectiveness Of Upper-divmentioning
confidence: 99%